Penetapan Kadar Flavonoid Total Ekstrak Etanol Umbi Wortel (Daucus Corata L.) Dengan Metode Spektrofotometri UV-VIS - Husnani Husnani (STIKes Ibnu Sina Ajibarang, 2023)
Empirically the Daucus corata L. tuber was rich in vitamin A which is necessary to maintain eye health, epithelial tissue and maintain tissue in the epidermis. The purpose of this research was to determine the total flavonoids levels of Daucus corata L. tuber extract with the UV-Vis spectrophotometry method using quercetin as a standard. In this research the calibration curve of standard solution of quercetin compounds was made by variation of concentration (6 μg/ml, 8 μg/ml, 10 μg/ml, 12 μg/ml, 14 μg/ml) then measured its absorption at a maximum wavelength of 429 nm. The total flavonoids content is calculated by the linear regression equation Y = 0, 02199x + 0, 11029 with r2 = 0, 98645. From the calculation result obtained total flavonoids levels of carrot tuber extract amounting to 0,707%/b b.